Perception of Physical Education students about remote classes in front of COVID-19: A case study (Research, Society and Development, 2021)
In face of COVID-19, many universities all over the word have adopted the online learning as a strategy for maintaining academic activities. In the sense, the aim of this study was to point the perception Physical Education students about remote classes. A total of 92 students from the physical education course in a private higher education institution participated in the study, with an average age of 25.07 (± 8.31) years. The data was collected through a form in Google Forms®. According to the results, the students believe that the adoption of remote classes was a good decision by the institution, and evaluated the adaptation of teachers as positive. The difficulties pointed out by the students involve problems with internet connection, personal, financial issues and adaptation to the new model. Thus, the importance of teacher training for online teaching is highlighted, as well as the institution's support for students who face problems in the process, in addition to the need for further studies in the area.